Diversity, distribution, and peasant selection of indigenous potato varieties in the Mantaro Valley, Peru: a biocultural process - Carney, H.J. (College of William and Mary in Virginia, 1979)
The central Andes represent the center of domestication for the potato. Biological and cultural factors contributing to the evolution and present-day diversity of native Andean potatoes are discussed. The frequency and distribution of native potatoes are examined at four different levels: field, family, village, and valley. A discussion of the selection process by natives is provided through an analysis of seed networks and ethnographic data. An assessment is made of the relative importance of the principal factors involved in peasant selection: culinary quality, resistance to pathogens, and yield. A model for the maintenance and amplification of the rich genetic base of potato varieties by Andean fanners is proposed.